Critical Review on Composite-Based Polymer Electrolyte Membranes toward Fuel Cell Applications: Progress and Perspectives - Wani A.A.; Shaari N.; Kamarudin S.K.; Raduwan N.F.; Yusoff Y.N.; Khan A.M.; Yousuf S.; Ansari M.N.M. (American Chemical Society, 2025)
Clean energy technologies, such as proton-exchange membrane fuel cells (PEMFCs), have emerged as viable alternatives to fossil fuels to produce energy, which has the added benefit of reducing environmental footprints. However, their broad use has been impeded by the performance, durability, and efficiency limitations of PEMFCs. A better knowledge of the compositions and architectures of PEMFCs may lead to enhancement in their durability and efficiency. The design, engineering, and well-architectured composite membranes retain water content in the polymer matrices and reduce the ohmic losses while operating at elevated temperatures. Researchers have been working on composite polymer electrolyte membranes (PEMs) in recent years to overcome the challenging issues currently faced in commercializing PEM technology. Achieving effective operations at higher working temperatures while retaining the physical and chemical characteristics of PEMs is one of the critical challenges. Herein, we outline the critical requirements for the composite membranes, molecular dynamic simulations, functional characteristics, and challenges that prevent the commercial application of PEMs for PEMFCs. More recent studies have focused on improving PEMs by composite material changes to address shortcomings in proton conductivity and stability. In this review, we delve into some of the latest innovations in PEMFC membranes, focusing on hybrid membranes that combine various inorganic, organic, and hybrid fillers with pristine polymeric membranes, such as Nafion, sulfonated polysulfone, polyaniline, polybenzimidazole, etc. This review also evaluates the fundamental steps utilized to develop novel sustainable composite membranes and how they stack up against current standards in PEM fuel cells. Furthermore, challenges to overcome in the advancement of PEMs toward real-world applications and future prospective research paths are also proposed. ? 2024 American Chemical Society.